2015
DOI: 10.1063/1.4905084
|View full text |Cite
|
Sign up to set email alerts
|

Landau superfluids as nonequilibrium stationary states

Abstract: We define a superfluid state to be a nonequilibrium stationary state (NESS), which, at zero temperature, satisfies certain metastability conditions, which physically express that there should be a sufficiently small energy-momentum transfer between the particles of the fluid and the surroundings (e.g., pipe). It is shown that two models, the Girardeau model and the Huang-Yang-Luttinger (HYL) model describe superfluids in this sense and, moreover, that, in the case of the HYL model, the metastability condition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…We showed that current-carrying states cannot be thermal equilibrium states (theorem 1). In the case of superfluidity, it was demonstrated, together with results of [Wre15a], that ground states cannot be equilibrium states if a certain condition on the limit points (possibly along subsequences) of the energy-momentum spectrum of finite systems is met (corollary 1), and that in the latter case the systems describe non-equlibrium stationary states (NESS). In the Girardeau-Lieb-Liniger model it was shown that the conditions of corollary 1 are indeed met, and that the energy spectrum of the infinite system is unbounded from below (proposition 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We showed that current-carrying states cannot be thermal equilibrium states (theorem 1). In the case of superfluidity, it was demonstrated, together with results of [Wre15a], that ground states cannot be equilibrium states if a certain condition on the limit points (possibly along subsequences) of the energy-momentum spectrum of finite systems is met (corollary 1), and that in the latter case the systems describe non-equlibrium stationary states (NESS). In the Girardeau-Lieb-Liniger model it was shown that the conditions of corollary 1 are indeed met, and that the energy spectrum of the infinite system is unbounded from below (proposition 1).…”
Section: Resultsmentioning
confidence: 99%
“…Since, for v satisfying (1.42.1), ǫ 1 ( k i ) + v · k i − k 2 i /2 ≥ 0 for all i = 1, · · · , r, and similarly for the other excitations (excluding the umklapp excitations, which we have shown to be absent), it follows that the restriction of H N,L − E 0 N,L + v · P N,L to R c,d N,L is positive, which is (1.36.2). The fact that the subspace R c,d N,L does not shrink to the empty set in the thermodynamic limit, i.e., (1.36.3), is easily seen to be true for any r ≥ 1, see [Wre15a].…”
Section: Consider Nowmentioning
confidence: 99%
See 3 more Smart Citations